A Scalable Free‐Standing V2O5/CNT Film Electrode for Supercapacitors with a Wide Operation Voltage (1.6 V) in an Aqueous Electrolyte. (14th June 2016) - Wu, Jiabin; Gao, Xiang; Yu, Huimin; Ding, Tianpeng; Yan, Yixin; Yao, Bin; Yao, Xu; Chen, Dongchang; Liu, Meilin; Huang, Liang
Abstract : While vanadium oxides have many attractive pseudocapacitive features for energy storage, their applications are severely limited by the poor electronic conductivity and low specific surface area. To overcome these limitations, a scalable, free‐standing film electrode composed of intertwined V2 O5 nanowires and carbon nanotubes (CNTs) using a blade coating process has been prepared. The unique architecture of this hybrid electrode greatly facilitates electronic transport along CNTs while maintaining rapid ion diffusion within V2 O5 nanowires and fast electron transfer across the V2 O5 /CNTs interfaces. When tested in a neutral aqueous electrolyte, this hybrid film electrode demonstrates a volumetric capacitance of ≈460 F cm −3 . Moreover, a symmetric capacitor based on two identical film electrodes displays a wide operation voltage window of 1.6 V, delivering a volumetric energy density as high as 41 Wh L −1 . Abstract : A scalable free‐standing V2 O5 /carbon nanotube film is prepared through blade coating process. This film has demonstrated great electrochemical performance with a volumetric capacitance around 460 F cm −3 .